2012
DOI: 10.1128/ec.00044-12
|View full text |Cite
|
Sign up to set email alerts
|

The RAM Network in Pathogenic Fungi

Abstract: The regulation of Ace2 and morphogenesis (RAM) network is a protein kinase signaling pathway conserved among eukaryotes from yeasts to humans. Among fungi, the RAM network has been most extensively studied in the model yeast Saccharomyces cerevisiae and has been shown to regulate a range of cellular processes, including daughter cell-specific gene expression, cell cycle regulation, cell separation, mating, polarized growth, maintenance of cell wall integrity, and stress signaling. Increasing numbers of recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 85 publications
0
71
0
9
Order By: Relevance
“…The RAM signaling pathway regulates a variety of cellular processes in both model and pathogenic fungi (4,45). The best-characterized functions of the RAM pathway are those associated with the transcription factor Ace2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RAM signaling pathway regulates a variety of cellular processes in both model and pathogenic fungi (4,45). The best-characterized functions of the RAM pathway are those associated with the transcription factor Ace2.…”
Section: Discussionmentioning
confidence: 99%
“…Because Ace2 is well known to play an important role in daughter cell transcriptional regulation (17,18,45), we were interested in whether the loss of Ace2 function would have an effect on the emergence of yeast from hyphae. Interestingly, the number of emerging yeast from ace2⌬/⌬ hyphae does not appear to differ from that of the wild type, indicating that Ace2 is not required for the budding process (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…5). The protein kinase Cbk1 and the transcription factor Ace2, which participate in the RAM (regulation of Ace2 and morphogenesis) pathway (54), are major regulators of wall and secreted proteins. The expression levels of both CHT3 and ENG1 decrease about 3-fold when ACE2 is knocked out (55).…”
Section: Fig 2 Relative Quantification Of Wall Proteins Using Ft-ms Andmentioning
confidence: 99%
“…Although it has been clearly linked to cell cycle and to daughter cell-specific gene expression (Saputo et al 2012;Weiss 2012), little is known regarding the potential function of the RAM pathway within other pathways that regulate cell morphogenesis and polarity. Our screens identified two genes that interact with CBK1 and are related, or are potentially related, to Cdc42 function.…”
Section: Cbk1 Interacts With Two Genes Related To Cell Polarity Throumentioning
confidence: 99%
“…The RAM pathway is centered on the Ndr/Lats family protein kinase Cbk1 (FungiDB: orf19.4909 ) and its transcription factor substrate Ace2 (FungiDB: orf19.6124 ). In addition to these two effector proteins, the RAM network includes Mob2, a Cbk1-binding protein required for kinase activity; Kic1, a kinase of unclear function; and the accessory proteins Tao3, Hym1, and Sog2 (Saputo et al 2012). Recent work has shown that Cbk1 also phosphorylates Bcr1 (FungiDB: orf19.723 ), a transcription factor involved in biofilm formation (Gutierrez-Escribino et al 2012), and the Fkh2, a forkhead transcription factor (Grieg et al 2015), involved in morphogenesis.…”
mentioning
confidence: 99%